2015
DOI: 10.1016/j.combustflame.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

LES study of deflagration to detonation mechanisms in a downsized spark ignition engine

Abstract: International audienceUsing 15 LES cycles of a high load / low speed spark ignition engine operating point, two different fresh gases autoignition regimes called knock and super-knock are analyzed. A direct " a posteriori " analysis of pressure waves and autoignition heat release observed in LES is proposed. It reveals that low to moderate knock intensity, corresponding to late spark timings (ST) is characterized by one or several random autoignition (AI) spots which consume the surrounding fresh gases without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 24 publications
7
70
0
Order By: Relevance
“…Following the earlier employment of the detonation peninsula [5][6][7][8][9][10], it has been used in a combined experimental engine and LES study to demonstrate how increasing spark advance, and the associated increasingly severe engine knock, cause the corresponding engine cycle loci to cross the threshold into the detonation peninsula [30].…”
Section: Engine Performance and The Detonation Peninsulamentioning
confidence: 99%
“…Following the earlier employment of the detonation peninsula [5][6][7][8][9][10], it has been used in a combined experimental engine and LES study to demonstrate how increasing spark advance, and the associated increasingly severe engine knock, cause the corresponding engine cycle loci to cross the threshold into the detonation peninsula [30].…”
Section: Engine Performance and The Detonation Peninsulamentioning
confidence: 99%
“…On the U/K diagram in [5], U is expressed in terms of both the Karlovitz stretch factor, K, which embodies the laminar burning velocity, ul, the integral length scale of the turbulence, l, the kinematic viscosity  , and also of the strain rate Markstein number, Masr, where…”
Section:  and The U/k Diagrammentioning
confidence: 99%
“…Other regimes of auto-ignitive combustion can also be indicated on the   / diagram, including those of benign controlled auto-ignition. Recently, Robert et al [5] have demonstrated how the diagram shows increasing the spark advance, increases the number of operational loci moving to within the peninsula, with increasingly severe engine knock.…”
Section: Introductionmentioning
confidence: 99%
“…[40]. Formation of H 2 O 2 is observed at the flame front, which is a typical characteristics of hydrocarbon flames but the mass fraction of H 2 O 2 reveals that most of the end gas region has started reacting and undergoes decomposition phase, leading to knock as shown in Figure A3.…”
Section: Effect Of Hot Spot Timing On Pre-ignition (Case a Case B Anmentioning
confidence: 99%